La cámara Gesell como medio de prueba en el ordenamiento procesal peruano - Escobar Antezano, Carlos Alfredo (2021)
The Gesell chamber is a forensic examination with scientific tendency that has to be practiced by psychologists and social workers. It has to be presented before a criminal judge. Its purpose is to receive the victim’s testimony and to determine their psychological damage. The psychologists must build upon their expertise, the victim’s knowledge and the truthfulness, memory and coherence of the victim’s story, which must be debated during the trial. The right to defense of the accused must be guaranteed, allowing for the intervention of an expert from the defense during the forensic examination. The victim’s declaration must be taken only once, in order to avoid further suffering.